Synthesis and application of supported metallic and multi-metallic oxides nanoparticles for in-situ upgrading and inhibition of formation damage (2015)
With the increasing world energy demand and the subsequent decrease in the world's easy-access oil supplies, conventional oil, the energy industry is increasingly turning to unconventional resources to recover oil, such as heavy and extra heavy oil and meet the world energy demand. However, in the current context, upgrading and recovery of heavy oil are highly energy and water intensive that requires a substantial capital and operating cost and consequently results in environmental footprints. In addition, asphaltenes are one of the most difficult problems to overcome in oil production and processing. The presence of asphaltenes in crude oil, and consequently, the adsorption and deposition of asphaltenes on the rock surfaces, affects the rock properties, such as porosity, permeability, and wettability. An alternative to the current upgrading, mitigate/inhibit asphaltene-related problems and enhance recovery processes is the potential employment of nanoparticle technology at reservoir conditions. This thesis aims at synthesize and apply metallic and/or multi-metallic oxides (e.g, Ni, and Pd) supported nanoparticles that have high adsorption selectivity and catalytic activity towards heavy hydrocarbons like asphaltenes. This study should provide a better insight on the influence of the adsorption process on the catalytic activity of the nanoparticles and give a better understanding about the use of nanotechnology for in-situ upgrading of heavy and extra-heavy oils and inhibition of formation damage.